2014
DOI: 10.1111/modl.12086
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of L2–L2 and L2–Heritage Learner Interactions in Spanish Language Classrooms

Abstract: Conversational interaction studies have typically focused either on second language (L2) learners participating in native speaker–nonnative speaker (NS–NNS) dyads or in NNS–NNS dyads. This study analyzes the task‐based interactions of 26 naturally occurring learner dyads in an intermediate‐level, university Spanish language classroom, 13 of which were matched L2 learner dyads and 13 of which were mixed L2 learner–heritage learner (HL) dyads. Specifically, the study compared the two dyad types to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 55 publications
2
47
2
1
Order By: Relevance
“…Although meta‐analytic syntheses of research have shown consistent benefits for recasts and negotiated interaction (Li, ; Mackey & Goo, ; Russell–Valezy & Spada, ), such broad generalizations may have little to say about implementation in specific contexts, given the variation in individual results. Furthermore, the claim that attention to L2 form would be best achieved through ad hoc reactive feedback has been undercut by evidence that (a) learners often fail to correct their peers on grammatical accuracy, particularly when their errors do not affect comprehensibility (Adams, Nuevo, & Egi, ; Bowles, Adams, & Toth, ; Buckwalter, ), and (b) tasks requiring learners to develop or apply elaborate explicit understandings of L2 structural patterns have positive outcomes on subsequent language use (Moranski & Toth, 2016; Negueruela & Lantolf, ; Swain et al., ). As social approaches to L2 development have gained interest since the turn of the millennium, proponents of the interaction hypothesis have begun to acknowledge the importance of social and pragmatic, contextual factors in explaining variability in learning outcomes (Ellis & Sheen, ; Mackey, ; Philp & Mackey, )…”
Section: Theoretical Explanations For the Impact Of Pedagogymentioning
confidence: 99%
“…Although meta‐analytic syntheses of research have shown consistent benefits for recasts and negotiated interaction (Li, ; Mackey & Goo, ; Russell–Valezy & Spada, ), such broad generalizations may have little to say about implementation in specific contexts, given the variation in individual results. Furthermore, the claim that attention to L2 form would be best achieved through ad hoc reactive feedback has been undercut by evidence that (a) learners often fail to correct their peers on grammatical accuracy, particularly when their errors do not affect comprehensibility (Adams, Nuevo, & Egi, ; Bowles, Adams, & Toth, ; Buckwalter, ), and (b) tasks requiring learners to develop or apply elaborate explicit understandings of L2 structural patterns have positive outcomes on subsequent language use (Moranski & Toth, 2016; Negueruela & Lantolf, ; Swain et al., ). As social approaches to L2 development have gained interest since the turn of the millennium, proponents of the interaction hypothesis have begun to acknowledge the importance of social and pragmatic, contextual factors in explaining variability in learning outcomes (Ellis & Sheen, ; Mackey, ; Philp & Mackey, )…”
Section: Theoretical Explanations For the Impact Of Pedagogymentioning
confidence: 99%
“…Among the few studies that have addressed HL learners’ response to pedagogical interventions, a research strand of task‐based peer interaction studies has emerged to better understand the nature of HL and second language (L2) peer interactions, and its effects on language performance and linguistic focus (Blake & Zyzik, ; Bowles, ; Bowles, Adams, & Toth, ; Henshaw, ). Due to the nature of pedagogic tasks that have the capacity to draw on learners’ linguistic and sociocognitive resources during interaction, these studies have demonstrated that tasks can serve as a vehicle to examine how HL learners deploy these resources to engage in authentic communicative events.…”
mentioning
confidence: 99%
“…Bowles (2011) found that L2 Spanish learners were very accurate with spelling and accent placement whereas heritage learners were not in a mixed classroom at an advanced level of Spanish. Although orthography should be taught to both student populations, heritage learners need more work on written accuracy (Kagan and Dillon, 2001).…”
Section: Similarities and Differences Between L2 And Heritage Learnermentioning
confidence: 90%
“…For heritage learners of Spanish, the same trend is found. In fact, there is research that shows that when both student populations are mixed in the same classroom, heritage learners rely on their L2 classmates for orthography (spelling and accentuation) whereas L2 learners rely on the heritage ones for vocabulary and grammar (Bowles, 2011).…”
Section: Similarities and Differences Between L2 And Heritage Learnermentioning
confidence: 99%